2017
DOI: 10.3390/molecules22050707
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Terrestrial Environments for Bacterial Polyketides

Abstract: Bacterial polyketides are highly biologically active molecules that are frequently used as drugs, particularly as antibiotics and anticancer agents, thus the discovery of new polyketides is of major interest. Since the 1980s discovery of polyketides has slowed dramatically due in large part to the repeated rediscovery of known compounds. While recent scientific and technical advances have improved our ability to discover new polyketides, one key area has been under addressed, namely the distribution of polyket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 262 publications
(342 reference statements)
0
11
0
Order By: Relevance
“…The metabolic pathways involving the metabolism of terpenoids and polyketides was only detected in proximal colon mucosal scrapings. Terpenoids and polyketides are large families of active natural compounds produced by a wide variety of living form including bacteria [65,66] suggesting that the emergence of this pathway in our mucosal samples could be due to differences in the relative abundances of other metabolic routes. In the distal colon segments, the relative abundance of pathways belonging to amino acid, carbohydrate, lipid and glycan metabolism and biosynthesis of secondary metabolites is increased compared to cecum and proximal colon area potentially due to lower level of host-microbiota crosstalk in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic pathways involving the metabolism of terpenoids and polyketides was only detected in proximal colon mucosal scrapings. Terpenoids and polyketides are large families of active natural compounds produced by a wide variety of living form including bacteria [65,66] suggesting that the emergence of this pathway in our mucosal samples could be due to differences in the relative abundances of other metabolic routes. In the distal colon segments, the relative abundance of pathways belonging to amino acid, carbohydrate, lipid and glycan metabolism and biosynthesis of secondary metabolites is increased compared to cecum and proximal colon area potentially due to lower level of host-microbiota crosstalk in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Bioprospecting for natural compounds from microorganisms dwelling in poorly explored and extreme environments has gained renewed interest [ 1 , 2 ], boosted by the need to fight resistance to compounds currently used as antimicrobials, herbicides, antivirals, and anticancer agents [ 3 ]. Caves, despite being highly oligotrophic environmental niches, support rich and diverse microbial life, a phenomenon called “the Paradox of the Plankton”, which suggests that, in spite of limited nutrient resources, an unexpectedly wide range of species coexist [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on an abandoned coal mine in South Korea found eight antimicrobial compounds from a Streptomycete isolate exhibited moderate activity against M. luteus , E. hirae , and methicillin resistant Staphylococcus aureus (MRSA) (Park et al, 2014). Alkaline mines have also been found to host microorganisms capable of antimicrobial production (Hill et al, 2017). A Nocardiopsis sp.…”
Section: Mining For Antimicrobialsmentioning
confidence: 99%